Discovery of life in Jack Kerouac‟s Novels - Paulina J, Christy (International Journal of Psychosocial Rehabilitation, 2020)
The Literature of the Beat Generation was the driving force behind its success in American society. The writers, especially Jack Kerouac captured the real tone and landscape of America and adopted a unique artistic style that best reflected the American cultures through their writings and expressions. Kerouac often focuses on writings about his personal experiences through the newly formulated technique called spontaneous prose. The passages had all the dimensions of life with every image and every memory put down in words. This wild form of writing was “a free association technique” (Charter xxv), which he referred to as spontaneous prose. He made a close study of all the friends he meets on the journey of life, among whom Neal Cassady was the man he dealt much upon in his novels. Cassady’s metaphysical study was in close relationship to the general America.